Microbial interactions play an important role in regulating the effects of plant species on soil bacterial diversity - Wang, Yajun; Ma, Lan; Liu, Ziyang; Chen, Jingwei; Song, Hongxian; Wang, Jiajia; Cui, Hanwen; Yang, Zi; Xiao, Sa; Liu, Kun; An, Lizhe; Chen, Shuyan (Frontiers in Microbiology, 2022)
Plant species and microbial interactions have significant impacts on the diversity of bacterial communities. However, few studies have explored interactions among these factors, such the role of microbial interactions in regulating the effects of plant species on soil bacterial diversity. We assumed that plant species not only affect bacterial community diversity directly, but also influence bacterial community diversity indirectly through changing microbial interactions. Specifically, we collected soil samples associated with three different plant species, one evergreen shrub (Rhododendron simsii) and the other two deciduous shrubs (Dasiphora fruticosa and Salix oritrepha). Soil bacterial community composition and diversity were examined by high-throughput sequencing. Moreover, soil bacterial antagonistic interactions and soil edaphic characteristics were evaluated. We used structural equation modeling (SEM) to disentangle and compare the direct effect of different plant species on soil bacterial community diversity, and their indirect effects through influence on soil edaphic characteristics and microbial antagonistic interactions. The results showed that 1) Plant species effects on soil bacterial diversity were significant; 2) Plant species effects on soil microbial antagonistic interactions were significant; and 3) there was not only a significant direct plant species effect on bacterial diversity, but also a significant indirect effect on bacterial diversity through influence on microbial antagonistic interactions. Our study reveals the difference among plant species in their effects on soil microbial antagonistic interactions and highlights the vital role of microbial interactions on shaping soil microbial community diversity.